Fast-Developing Dynamic Radiative Thermal Management: Full-Scale Fundamentals, Switching Methods, Applications, and Challenges - Long Xie; Xuechuan Wang; Yageng Bai; Xiaoliang Zou; Xinhua Liu (Nano-Micro Letters)
Highlights This review comprehensively summarizes the current state-of-the-art in dynamic radiative thermal management technology. In-depth discussion of the basic principles of dynamic radiative thermal management technology, design strategies, and a list of related applications are presented. An in-depth look at the challenges facing dynamic radiative thermal management technology, providing potential solutions for the future direction of the field.